2013
DOI: 10.1364/oe.21.013748
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic stability of quantum cascade lasers against optical feedback

Abstract: We study the time dependence of the optical power emitted by terahertz and mid-IR quantum cascade lasers in presence of optical reinjection and demonstrate unprecedented continuous wave (CW) emission stability for strong feedback. We show that the absence of coherence collapse or other CW instabilities typical of diode lasers is inherently associated with the high value of the photon to carrier lifetime ratio and the negligible linewidth enhancement factor of quantum cascade lasers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 26 publications
0
66
0
Order By: Relevance
“…Using this model, we reproduce all optical feedback-related phenomena, including the compounding effect of re-injected photons on laser electro-optical dynamics, external cavity oscillations [36], altered threshold current [37,38], and modulation bandwidth [39]. In most lasers, changes in temperature or drive current [40] cause a slight perturbation in the emission frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Using this model, we reproduce all optical feedback-related phenomena, including the compounding effect of re-injected photons on laser electro-optical dynamics, external cavity oscillations [36], altered threshold current [37,38], and modulation bandwidth [39]. In most lasers, changes in temperature or drive current [40] cause a slight perturbation in the emission frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have been performed recently and interpreted using the Lang and Kobayachi equations modeling a conventional semiconductor laser subject to a delayed optical feedback [28]. The authors determined the first oscillatory instability (Hopf bifurcation) and explored the stabilizing effect of a large photon to carrier lifetime ratio.…”
Section: Discussionmentioning
confidence: 99%
“…In the mid-IR, although QCLs are much more resistant to optical feedback than their interband counterparts due to the lower α-factor, 6 it has been shown that they still exhibit the same behavior in terms of changes of output power, threshold current and optical spectrum. 7 Furthermore, chaotic emission from a QCL under optical feedback has recently been evidenced.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%